IMPROVEMENT OF THE OUTCOME OF PLASTIC SURGICAL OPERATIONS FOR MODERATE-SEVERE GENITAL PROLAPSE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
We conducted a comparative analysis of the results of treatment of 102 patients with genital prolapse of the III and IV degrees. The use of metostyle contributed to an increase in the rate of tissue regeneration and improved the effectiveness of surgical treatment of patients with prolapse of the internal genital organs. The use of metostyle allowed to reduce the duration of treatment by 1.6±0.3 days.